2000
DOI: 10.1038/sj.gt.3301143
|View full text |Cite
|
Sign up to set email alerts
|

Tri-iodothyronine and a deleted form of hepatocyte growth factor act synergistically to enhance liver proliferation and enable in vivo retroviral gene transfer via the peripheral venous system

Abstract: Retroviral vectors integrate into the target cell genome in a stable manner and therefore offer the potential for permanent correction of the genetic diseases that affect the liver. These vectors, however, usually require cell division to occur in order to allow provirus entry into the nucleus. We have explored clinically acceptable methods to improve the efficiency of retroviral gene transfer to the liver, which avoid the need for liver damage. Tri-iodothyronine (T3) and recombinant hepatocyte growth factor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This is the first demonstration that injection of purified HGF protein prior to an RV can result in long-term expression of a therapeutic gene, although others have previously demonstrated that HGF potentiates RV transduction, [38][39][40][41] and we showed that intramuscular injection of an adenoviral vector expressing HGF increased RV transduction and improved clinical efficacy in MPS VII mice. 42 The level of cFIX achieved at late times after transfer into adult BALB/c mice (1.75 g/mL) was only 19% of the average value observed in 3 different stains after transfer into neonatal mice (9.3 g/mL) despite use of the same dose of RV per kg body weight.…”
Section: Hgf-potentiated Rv Transfer Into Adult Mice Achieves Therapementioning
confidence: 97%
See 2 more Smart Citations
“…This is the first demonstration that injection of purified HGF protein prior to an RV can result in long-term expression of a therapeutic gene, although others have previously demonstrated that HGF potentiates RV transduction, [38][39][40][41] and we showed that intramuscular injection of an adenoviral vector expressing HGF increased RV transduction and improved clinical efficacy in MPS VII mice. 42 The level of cFIX achieved at late times after transfer into adult BALB/c mice (1.75 g/mL) was only 19% of the average value observed in 3 different stains after transfer into neonatal mice (9.3 g/mL) despite use of the same dose of RV per kg body weight.…”
Section: Hgf-potentiated Rv Transfer Into Adult Mice Achieves Therapementioning
confidence: 97%
“…57 However, most of the concerns noted above for neonatal gene transfer need to be addressed prior to implementing this approach in human adults. In addition, it would be necessary to demonstrate that transient administration of HGF is safe, although it has been efficacious and well tolerated in animal models of liver disease 58 and no overt adverse effects were noted in this or previous [38][39][40][41][42] studies. Finally, immune modulation may be necessary at the time of gene therapy, given that antibody responses occurred in all animals that were transduced as adults.…”
Section: Hgf-potentiated Rv Transfer Into Adult Mice Achieves Therapementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a number of studies have shown that pretreatment with growth factors can enable retroviral gene transfer to the liver to be achieved. HGF, KGF, T3 as well as a combination thereof resulted in successful transduction of up to 7% of hepatocytes (12)(13)(14)(15). However, the clinical safety of some of these polypeptidic growth factors has not been documented.…”
mentioning
confidence: 91%
“…At least in experimental animals, an opportunity is provided by tri-iodothyronine which has proved to be a modulator of liver cell mass, acting as a primary mitogen for the liver (ie able to initiate hepatocyte proliferation in the intact liver). This was initially explored as a means of initiating DNA synthesis and rendering cells susceptible to retroviral gene transfer 7,8 (as discussed below). However, it has the interesting potential of increasing total liver cell mass, total DNA and total protein by inducing proliferation of cells, acting predominantly on hepatocytes in the mid-zonal area of the liver lobule.…”
Section: Growth Factors In Therapy For Liver Diseasementioning
confidence: 99%